2016
DOI: 10.1021/acs.inorgchem.5b02836
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and Mechanism of the Chlorite–Periodate System: Formation of a Short-Lived Key Intermediate OClOIO3 and Its Subsequent Reactions

Abstract: The chlorite-periodate reaction has been studied spectrophotometrically in acidic medium at 25.0 ± 0.1 °C, monitoring the absorbance at 400 nm in acetate/acetic acid buffer at constant ionic strength (I = 0.5 M). We have shown that periodate was exclusively reduced to iodate, but chlorite ion was oxidized to chlorate and chlorine dioxide via branching pathways. The stoichiometry of the reaction can be described as a linear combination of two limiting stoichiometries under our experimental conditions. Detailed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2017
2017
2018
2018

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
1
2
1
Order By: Relevance
“…The previous literature de facto accepted the existence of both the ortho–meta equilibrium as well as the dimerization, and these processes have frequently been invoked. There are many interests for different reactions of periodate, and our research group investigated some of them quite recently. Reactions with chlorite, bromide, thiosulfate, tetrathionate, iodide, pentathionate were soundly described, though during this research some contradictions were noticed between our experiments and the previous literature. Therefore, we decided to perform a complete reinvestigation of the periodate equilibrium in aqueous medium.…”
Section: Introductioncontrasting
confidence: 81%
“…The previous literature de facto accepted the existence of both the ortho–meta equilibrium as well as the dimerization, and these processes have frequently been invoked. There are many interests for different reactions of periodate, and our research group investigated some of them quite recently. Reactions with chlorite, bromide, thiosulfate, tetrathionate, iodide, pentathionate were soundly described, though during this research some contradictions were noticed between our experiments and the previous literature. Therefore, we decided to perform a complete reinvestigation of the periodate equilibrium in aqueous medium.…”
Section: Introductioncontrasting
confidence: 81%
“…This intermediate is similar to the intermediate proposed by Emeish (H 2 ClNO 5 ) but with one water molecule less, and it is analogous to other asymmetric intermediates recently proposed to explain reactions involving different halogen species, such as OClOIO 3 (proposed in the mechanism of the chlorite–periodate reaction), BrIO 3 or BrOIO 2 (proposed in the mechanism of the bromide–periodate reaction), and also with one of the first asymmetric intermediates, ClOClO, proposed by Taube and Dodgen …”
Section: Resultssupporting
confidence: 83%
“…During the equilibrium measurements, the pH of the chlorine dioxide stock solution was set to 5.55 by an acetic acid/acetate buffer, taking the p K a of acetic acid as 4.55 . The acetate concentration was kept constant at 1.0 M. In agreement with previous studies, the acetate buffer was found to be innocent of reacting directly with chlorine dioxide. The pH of the sodium chlorite stock solution was set to 11.0 by sodium hydroxide, and the ionic strength was adjusted by sodium perchlorate to 1.0 M. All of the solutions were precooled in a refrigerator. Before each measurement, the initial solutions were left to stand more than 15 min at thermostated conditions to reach the temperature of 7.0 ± 0.5 °C.…”
Section: Methodsmentioning
confidence: 54%